Radiation dose associated with coronary CT angiography and invasive coronary angiography: An experimental study of the effect of dose-saving strategies - Sabarudin, A.; Sun, Zhonghua; Ng, K. (Oxford University Press, 2012)
This study was conducted on a human anthropomorphic phantom to investigate the effective dose and entrance skin dose (ESD) in selected radiosensitive organs through invasive and computed tomography (CT) coronary angiography procedures using different dose-saving techniques. The effective dose was calculated as 2.49, 3.35 and 9.62 mSv, respectively, corresponding to three coronary CT angiography protocols, including prospective ECG gating and retrospective ECG gating with and without tube current modulation. In comparison, the effective dose was calculated as 7.26, 6.35, 5.58 and 4.71 mSv at four different magnifications acquired with invasive coronary angiography. The highest ESD was measured in the breast during the coronary CT angiography and in the thyroid gland during invasive coronary angiography. Although invasive coronary angiography produces lower radiation dose than coronary CT angiography, application of modified techniques in both CT and invasive coronary angiography is recommended in clinical practice for radiation dose reduction.